EMPREGO DO BIM 4D NA ELABORAÇÃO DO CRONOGRAMA DE OBRAS POR MEIO DE CUSTOMIZAÇÕES - Coelho, Larsson; Ulhoa, Cecile; Brandstetter, Maria Carolina (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
One of the great challenges of construction work planning and control is the failure of communication among all participants in the process and Building Information Modeling has been used to enable the improvement of this communication. This research seeks to facilitate the use of BIM in the planning of vertical residential works, from the link of work schedule with model's elements. The objective is to present the use of BIM 4D in the elaboration of the work schedule, through a customization. With the help of Information Technology, it is possible to automate the creation of the Work Breakdown Structure and the linking of the model's elements to the WBS's tasks. Through a model applied to a real case of residential project, the research contributes indicating that the time used in manual and repetitive tasks can be substituted for schedules's analysis, contributing to the improvement of the Construction work planning and, consequently, to the compatibilization between the stages of the process.